Pengembangan Instrumen Tracer Study Berbasis Cluster Sebagai Kontrol Mutu Lulusan Perguruan Tinggi - Muhamad Fakhrur Saifudin; Meita fitrianawati (Jurnal Penjaminan Mutu, 2021)
The purpose of this research is to develop a cluster-based tracer study instrument that can be used to measure the absorption rate of graduates based on competency. This type of research is development. This study uses the ADDIE development model (Analysis, Design, Development, Implementation and Evaluation) i. The product appraisal instrument uses a quality assessment sheet involving material experts and an evaluation sheet which is used to determine the responses of stakeholders and graduates regarding the use of the product being developed. The type of data obtained is data about the process of developing a cluster-based tracer study instrument from the input of experts and graduates. The data analysis of this research used process data analysis and product quality data analysis. The results of the study were based on a feasibility test based on the material validator, assessment, and language validator which were assigned to the graduate assessment instrument with the criteria of "very suitable". The results of field trials showed the feasibility of the instrument as a tool for evaluating graduates was 86.5% so that it could be used as an alternative in tracing studies. These results are used as the basis for determining the success of higher education institutions in producing quality graduates